HOME-BASED EXPERIMENT: STUDENTS’ RESPONSES ABOUT INDEPENDENT PRACTICUM AT HOME DURING ONLINE LEARNING - Putra, Nanda Syah; Desmiawati, Desi (Universitas Muhammadiyah Palembang, 2023)
This study aimed to reveal students’ responses to the implementation of home-based experiments on photosynthesis materials. The research sample consisted of 1 class that implemented home-based experiment learning, with the number of students involved being 26 students, which was determined using convenience sampling technique.The student response measurement scale used the Guttman scale, which demanded an unequivocal answer from the student to the given question. Students were given a choice of